2003
DOI: 10.1055/s-2003-38291
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Pancreatic Isoamylases in the Serum of Children with Choledochal Cyst

Abstract: Abnormal pancreatic isoamylases, especially P4 and P5, are found in the serum of patients with choledochal cyst, which would point to a reflux of pancreatic juice into the biliary tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Many previous studies of pancreaticobiliary maljunction demonstrated high levels of amylase and/or lipase in the bile as evidence of regurgitation of pancreatic juice into the bile duct (19)(20)(21)(22)(23)(24)(25)(26)(27). However, only five studies have documented activation of proenzymes in the bile under pancreaticobiliary maljunction (6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies of pancreaticobiliary maljunction demonstrated high levels of amylase and/or lipase in the bile as evidence of regurgitation of pancreatic juice into the bile duct (19)(20)(21)(22)(23)(24)(25)(26)(27). However, only five studies have documented activation of proenzymes in the bile under pancreaticobiliary maljunction (6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge has prompted us to look for abnormal pancreatic isoamylases in patients with CC. 7,8 With the same technique in the current study, we attempted to evaluate the diagnostic value of isoamylases for this rare subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,10 Isoamylases were separated in a standard electrophoresis cell on nitrocellulose membranes (Amersham, Piscataway, NJ) with a discontinuous buffer system. The anodal chamber contained TRIS base at 0.15 m/L titrated to a pH of 9.15 with boric acid.…”
Section: Determination Of Total Amylase Activity and Isoamylasesmentioning
confidence: 99%
See 2 more Smart Citations